Risky Dependency: Social Welfare and Dependency in French Policies on Aging - Lanoix, Monique (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
In this paper, I examine the policies put forward by the French government to address the increasing need for eldercare. I analyze two pivotal terms in these policies—dependency and solidarity—and I consider the proposal of Nicolas Sarkozy, France’s president from 2007 to 2012, to frame dependency as a fifth social risk.